Construção e representação da identidade de Alto Verde e La Boca. Trabalho conjunto entre a Rede Interinstitucional e Social Alto Verde e a Universidade Nacional do Litoral - Heinrich, Verónica (Universidad Nacional del Litoral, 2019)
This work is a shared reflection on the complex process of construction, narration and representation of identity in the Alto Verde and La Boca communities of the city of Santa Fe. From the perspective provided by the sustained presence of the National University of the Litoral in the territory –particularly in the 2006–2019 period– experiences, exchanges and products generated from the dialogue between territorial institutional actors, neighbors, management teams, teachers and university students are reported, given the need to make visible and value community resources and natural In this journey, the Alto Verde Inter–Institutional and Social Network plays a key role, as a mechanism for articulation between social organizations, neighbors and public policies. In this space, the university participates as one more actor, generating links between academic and institutional capacities and local social processes.From the reflexive rereading of different moments of this tour, it is proposed to share the diversity of contributions for the identification of the problem, actors involved, objectives and methodologies as well as conclusions learning and new challenges of this collective plot with the territory and for the University extension management.